Camera Alignment System for Face Detection - Mohd Rawi, Noor Aiman Zafira (Universiti Teknologi PETRONAS, 2016)
In the enrolment by a facial recognition system, the capture of the facial features is an important step in the enrolment process. The capture of the reference facial image is an important step where the positioning of the face where people have a tendency to turn or tilt their head and cause incorrect capture of facial image. In order to get the best capture of a person’s face, the person has to be standing in the correct position and look forward into the camera and hold for a while. Previous studies prove that even though some cameras have a large view field, it still cannot capture the face with the best resolution and sufficient for recognition. Surveillance cameras for example have a large view field because they acquired to monitor on large areas rather than focusing on faces. This will result in limitation in term of the number of pixels covered thereby downgrading the face matching process.